Pregnancy and Covid 19 Infection: Characteristics, Signs, Symptoms, and Impact on Maternal and Neonatal: Systematic Review - Purwatiningsih, Yuni; Lestyoningrum, Sinta Dewi; Wulandari, Aliesya Patricia (Universitas Aisyah Pringsewu, 2022)
The Covid 19 pandemic had a terrible impact on the health system, especially maternal and child health. Covid 19 and MERS infections lead to higher case fatality rates and more severe morbidity during pregnancy. Pregnant women and neonates are a group at risk for the severity of Covid 19 infection. This study aimed to review the characteristics, signs, symptoms, and impact on maternal and neonatal of pregnant women with positive Covid 19. We performed a systematic review to investigate pregnant women infected with Covid 19. Literature research was conducted using several search engines, including PubMed, Science Direct, and The Lancet, from January 1st, 2021 to March 31th, 2022. The articles were screened based on the inclusion and exclusion criteria based on the PRISMA guidelines. We included 8 studies, the number of pregnant women obtained was 1460 pregnant women with positive COVID 19, 1830 pregnant women with negative COVID-19, and 71 nonpregnant women with positive Covid 19. The average age of the mother is around 19-41 years, gestational age is between 25-41 weeks, and the common symptoms are fever, cough, difficulty breathing, or shortness of breath. The most common complications were premature birth and premature rupture of membranes; besides bleeding complications, preeclampsia and fetal distress were reported. The common symptoms are fever and cough, and the impact of maternal are preterm birth and premature rupture of the membranes. The effect of neonatal is low birth weight and premature. Abstrak: Pandemi Covid 19 memberikan dampak yang sangat buruk bagi sistem kesehatan, khususnya untuk kesehatan ibu dan anak. Infeksi Covid 19 dan MERS menyebabkan tingkat kematian kasus yang lebih tinggi dan tingkat morbiditas yang lebih parah selama kehamilan. Ibu hamil dan neonatus merupakan kelompok yang berisiko untuk terjadinya infeksi Covid-19 yang berat. Penelitian ini bertujuan untuk mengkaji karakteristik, tanda, gejala, dan dampak pada ibu dan bayi baru lahir dari ibu hamil yang positif Covid 19. Penelitian merupakan systematic review yang dilakukan untuk menyelidiki ibu hamil yang terinfeksi Covid 19. Penelitian ini dilakukan dengan melakukan pencarian literatur menggunakan beberapa database pencarian elektronik , antara lain PubMed, Science Direct, dan The Lancet yang dipublikasi pada satu tahun terakhir yaitu mulai 1 Januari 2021 dan 31 Maret 2022. Artikel yang diperoleh dilakukan screening berdasarkan kriteria inklusi dan eksklusi berdasarkan pedoman PRISMA. Terdapat 8 artikel penelitian yang kami masukkan kedalam penelitian ini yang telah sesuai dengan kriteria inklusi, jumlah ibu hamil yang didapat adalah 1460 ibu hamil positif COVID 19 dan 1830 ibu hamil negatif COVID-19. Rata-rata usia ibu sekitar 19-41 tahun, usia kehamilan antara 25-41 minggu, dan gejala yang umum adalah demam, batuk, sulit bernapas, atau sesak napas. Komplikasi yang paling umum adalah kelahiran prematur dan ketuban pecah dini, selain dari komplikasi perdarahan, preeklamsia dan gawat janin juga dilaporkan. Gejala yang umum adalah demam dan batuk, dan dampak dari ibu adalah kelahiran prematur dan ketuban pecah dini. Efek neonatus adalah berat badan lahir rendah dan prematur.